Trauma and Gambling: A Scoping Review of Qualitative Research - Monson, Eva; Villotti, Patrizia; Hack, Benjamin (Critical Gambling Studies, 2023)
Both gambling-related problems and trauma have long been associated with substantial costs for individuals, their families, and society. Existing reviews of research on the relationship between trauma and gambling have thus far been limited to quantitative work. A scoping review of published peer-reviewed qualitative research was conducted to synthesize existing research concerning the relationship between trauma and gambling. Relevant articles were identified through database searches in Ovid MEDLINE, APA PsycNET, PubMed, Scopus, PTSDpubs, and through hand sorting methods. English and French articles that comprised original qualitative research with results exploring the relationship between trauma and gambling were included. A total of 22 articles published between 2007 and 2022 were included in this review. Four major themes emerged during the narrative and thematic synthesis of the articles: (1) gambling as a consequence of trauma, (2) trauma as a consequence of gambling behavior, (3) cyclical relationship of trauma and gambling, and (4) healing from trauma and gambling-related harms. Future research would benefit from the use of qualitative methods in exploring the complex relationships between trauma and gambling.